Active inference, selective attention, and the cocktail party problem. (December 2021) - Holmes, Emma; Parr, Thomas; Griffiths, Timothy D.; Friston, Karl J.
Highlights: New generative model for selective attention during cocktail party listening. Computational 'lesions' in the model dissociate different errors during word report. We model different temporal hypotheses for preparatory attention. Temporal changes in precision are necessary to explain ERPs but not reaction times. CNV-like responses can be explained by subjective precision rather than action. Abstract: In this paper, we introduce a new generative model for an active inference account of preparatory and selective attention, in the context of a classic 'cocktail party' paradigm. In this setup, pairs of words are presented simultaneously to the left and right ears and an instructive spatial cue directs attention to the left or right. We use this generative model to test competing hypotheses about the way that human listeners direct preparatory and selective attention. We show that assigning low precision to words at attended—relative to unattended—locations can explain why a listener reports words from a competing sentence. Under this model, temporal changes in sensory precision were not needed to account for faster reaction times with longer cue-target intervals, but were necessary to explain ramping effects on event-related potentials (ERPs)—resembling the contingent negative variation (CNV)—during the preparatory interval. These simulations reveal that different processes are likely to underlie the improvement in reaction times and the ramping of ERPs that are associated with spatial cueing.